PERBANDINGAN AKTIVITAS ANTIBAKTERI Penicillium notatum ATCC 28089 DENGAN Penicillium sp. R1M YANG DIISOLASI DARI MANGROVE Sonneratia caseolaris - Asep Awaludin Prihanto (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
Mangrove Sonneratia caseolaris is a potential host for  endhopytic fungi that commonly produce strong dan unique antibiotic. The objective of the research was to compare the antibacterial activity of Penicillium notatum ATCC 28089 and endophytic fungus Penicillium sp. R1M isolated from Mangrove Sonneratia caseolaris. First step of the research was observation the growth curve of each isolate. Second step was isolation of their  metabolites to be used in the antibacterial activity assay against Staphylococcus aureus ATCC 9144 and Escherichia coli ATCC 8739. The results showed that both isolates indicated different growth curves. Penicillium sp. R1M experienced shorter adaptation phase, than P. notatum  ATCC 28089.  The secondary metabolites of  P. notatum ATCC 28089 was isolated on day 8, while those of Penicillium sp. R1M isolated on day 6. The result of antibacterial assay  confirmed  that the  extracts of mycelia Penicillium sp. R1M show inhibition diameter in the growth of S. aureus and E. coli  with 11.5 ± 0.6 mm and 10.6 ± 0.4, mm, respectively, while the medium extracts of  P. notatum ATCC 28089 were 9.3 ± 0.9 mm and 7.4 ± 0.1 mm, respectively. The  inhibitory zone diameter of  medium extracts. Penicillium sp. R1M against S. aureus and  E. coli were correspondingly 7.5 ± 0.1 mm and 7.1 ± 0.8 mm, while  the medium  extracts of P. notatum ATCC 28089 were 9.3 ± 0.6 mm and 7.4 ± 0.4 mm, respectively. Mycelial extracts of  Penicillium sp. R1M showed better antibacterial activity than those of  P. notatum ATCC 28089. On the other hand the medium extracts showed the opposite results.Keywords: antibacterial, Penicillium sp. R1M, Sonneratia caseolaris